2015
DOI: 10.1007/s11064-015-1693-z
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Tetrachloride Increases the Pro-inflammatory Cytokines Levels in Different Brain Areas of Wistar Rats: The Protective Effect of Acai Frozen Pulp

Abstract: Acai offers health benefits associated with its high antioxidante capacity, phytochemical composition, nutritional and sensory value. Therefore, the objective of this study was to evaluate the protective effect of acai frozen pulp on carbon tetrachloride (CCl4)-induced damage via modulation of anti- and pro-inflammatory cytokines in rat brain tissue. The rats were treated via oral (gavage) daily with water or acai frozen pulp for 14 days at a dose of 7 μL/g. On the 15th day, the animals in each group received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…HE is ascribed with hyperammonemia in the bloodstream that can pass via the blood-brain barrier (BBB) and causes damage to the brain tissue through oxidative stress, inflammatory response, and dysfunction of energy metabolism (de Souza Machado et al 2015) . It is well known that CCl 4 treatment can successfully stimulate liver injury and HE associated brain tissue damage (de Souza Machado et al 2015) . For confirmation, the current experiment revealed that serum levels of liver enzymes; ALT and AST were increased significantly in CCl 4induced mice compared to the vehicle group.…”
Section: Discussionmentioning
confidence: 99%
“…HE is ascribed with hyperammonemia in the bloodstream that can pass via the blood-brain barrier (BBB) and causes damage to the brain tissue through oxidative stress, inflammatory response, and dysfunction of energy metabolism (de Souza Machado et al 2015) . It is well known that CCl 4 treatment can successfully stimulate liver injury and HE associated brain tissue damage (de Souza Machado et al 2015) . For confirmation, the current experiment revealed that serum levels of liver enzymes; ALT and AST were increased significantly in CCl 4induced mice compared to the vehicle group.…”
Section: Discussionmentioning
confidence: 99%
“…Neural viability may supplementary be affected by drugs, neuroendocrine factors, or various substances [36]. Acai frozen pulp can prevent the carbon tetrachloride-induced increase of interleukins (ILs)-1β and -18, and tumour necrosis factor-α (TNF-α) in the brain tissue in vivo, potentially contributing to the improvement of HE and the overall disease status [11]. Minimal hepatic encephalopathy is the infraclinical stage of HE, and can significantly impact patients' quality of life; unfortunately, the diagnosis is difficult and relies on psychometric testing or magnetic resonance spectroscopy [48].…”
Section: Thyroid Cancermentioning
confidence: 99%
“…HE is ascribed with hyperammonemia in the bloodstream that can pass via the blood-brain barrier (BBB) and causes damage to the brain tissue 3 . The mechanism for brain injury associated with HE was reported to be through oxidative stress, in ammatory response, and dysfunction of energy metabolism 3 . It was previously documented that CCl 4 treatment can successfully stimulate liver injury along with HE associated brain tissue damage 3 .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for brain injury associated with HE was reported to be through oxidative stress, in ammatory response, and dysfunction of energy metabolism 3 . It was previously documented that CCl 4 treatment can successfully stimulate liver injury along with HE associated brain tissue damage 3 . For con rmation, the current experiment revealed that serum levels of liver enzymes; ALT and AST, elevated signi cantly in CCl 4 -induced mice when compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation